1999
DOI: 10.1097/00003246-199903000-00047
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for cerebral hypoperfusion during cerebral malaria

Abstract: Because jugular bulb venous oxygen saturation remained within the normal range, cerebral hyperemia seems to be an adaptive response to altered systemic determinants, which argues against a hemodynamic mechanism for altered consciousness during cerebral malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Cerebral hemodynamics is particularly difficult to compare because of few and apparently conflicting findings in human studies. Transcranial Doppler sonography studies showed mostly normal and sometimes increased CBF velocities in CM patients, [12][13][14][15] although wide ranges and large differences between brain hemispheres were observed. In the larger study, although 30% of children initially presented increased CBF velocities, the children with fatal outcomes presented low CBF velocity recordings after admission.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Cerebral hemodynamics is particularly difficult to compare because of few and apparently conflicting findings in human studies. Transcranial Doppler sonography studies showed mostly normal and sometimes increased CBF velocities in CM patients, [12][13][14][15] although wide ranges and large differences between brain hemispheres were observed. In the larger study, although 30% of children initially presented increased CBF velocities, the children with fatal outcomes presented low CBF velocity recordings after admission.…”
Section: Discussionmentioning
confidence: 93%
“…7,10 Ischemic damage has also been shown in children with CM and was associated with severe neurological sequelae. 11 On the other hand, transcranial Doppler sonography studies showed normal or even increased cerebral blood flow (CBF) velocities [12][13][14][15] in large arteries during CM, which associated with microcirculatory obstruction has been suggested to increase cerebral blood volume leading to intracranial hypertension. 16 Alternatively, collateral flow has been proposed as a mechanism to reconcile the findings of normal or increased CBF velocities and impaired perfusion, 17 an interpretation supported by findings of hyperdynamic flow in capillaries adjacent to obstructed vessels.…”
mentioning
confidence: 99%
“…This may be another reason why relatively crude measurements of perfusion have yielded conflicting results about blood flow in human CM. Transcranial Doppler ultrasound failed to demonstrate decreased blood flow in human CM 56 ; however, the resolution of the technique may not be sufficient to detect localized foci of hypoperfusion and occlusion. Low resolution has also proved limiting in magnetic resonance imaging in patients with CM.…”
Section: Hypoxia and Cerebralmentioning
confidence: 88%
“…The nature of hemodynamics disturbances in human CM is unclear, with conflicting results showing either vasodilatation or stenosis of brain arteries (Newton et al, 1997;Clavier et al, 1999). Vessel vasodilatation was thought to cause brain swelling (Looareesuwan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%